Dealing with COVID‐19 Pandemic in Complex Societal System for Resilience Study: A Systems Approach. Issue 1 (20th September 2021) - Wang, Bijun; Mansouri, Mo
Abstract: The continuing spread of COVID‐19 has triggered a global health crisis with raising a series of problems in healthcare, economics, policymaking and environment, which significantly affected the resilience of the whole societal system. We emphasize the societal system, as an adaptive and complex system, has a fundamental impact on the spread of the virus linked to individual behavior change and disaster governance system. This paper combined system thinking and resilience thinking to visualize the complexity and comprehend the governance system under global pandemic threats towards recovering the resilient society. We underline the societal system can be affected by the pandemic, and in turn, impinge on the individual behaviors and governance with a proposed multi‐stage and multi‐scalar framework dealt with the process from crisis to recovery. Meanwhile, a qualitative system dynamics model is proposed inspired by the general Susceptible‐Infected‐Recovery (SIR) model with multiple interactions and interdependency of intervention policies, human psychological factors and mobility‐related factors to explore the influence on the societal system with time effect. Through this perspective, we should enhance the sense of crisis and integrate resilience thinking into the current hazards and recovery process combined with the interconnectedness among societal system in the future.